1994
DOI: 10.1007/bf02768241
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of cystolithotripsy and extracorporeal shock wave therapy for bladder stones

Abstract: This study compares the safety and efficacy of mechanical cystolithotripsy (MCLT) and extracorporeal shock wave lithotripsy (ESWL) in the treatment of vesical stones. In the last four years we have treated 144 bladder lithiasis patients with MCLT (86; group A) and ESWL (58; group B). All patients in group A were treated under spinal anaesthesia while 47 patients in group B needed intravenous sedation. The early complication rates in groups A and B were 19.7 and 6.8%, respectively. The corresponding mean hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 13 publications
0
11
0
4
Order By: Relevance
“…Today it is a rarely used method. In recent studies, comparing the effectivity of OC with endourological procedures in treating large bladder stones, it was concluded that OC has a 100% stone-free rate at one setting, similar operation time but a longer hospital stay [9,11]. Nowadays, OC should be the main treatment modality in patients with heavy stone burden, abnormal anatomy preventing safe access for endourological methods or who are undergoing open prostatectomy and diverticulectomy [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Today it is a rarely used method. In recent studies, comparing the effectivity of OC with endourological procedures in treating large bladder stones, it was concluded that OC has a 100% stone-free rate at one setting, similar operation time but a longer hospital stay [9,11]. Nowadays, OC should be the main treatment modality in patients with heavy stone burden, abnormal anatomy preventing safe access for endourological methods or who are undergoing open prostatectomy and diverticulectomy [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…These minimally invasive surgical procedures significantly increased the success rates of bladder stone treatment however, complication rates and operation time change according to the treatment modality. In these surgical techniques, bladder stones were removed via transurethral or suprapubic routes [9]. Generally, intervention through transurethral way is made by using a cystoscope or nephroscope [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Secondly, there has also been some controversies regarding the proper patient positioning during the ESWL session. Some authors suggested a prone position 17 while others recommended conducting the session in a supine position. 10 Some authors prefered supine position because they assumed that in prone position, the sacrum might hinder stone fragmentation to some extent.…”
Section: 312-14mentioning
confidence: 99%
“…Additionally, transurethral approach also has several additional disadvantages such as longer operating time, hematuria, risk of bladder perforation, and potential urethral injury as their disadvantages. 7,17 ESWL, on the contrary, is a non-invasive modality that utilizes high energy acoustic pulses generated outside the body. 18 The effective applications of ESWL in disintegrating both radiopaque and radiolucent renal stones (e.g.…”
Section: 312-14mentioning
confidence: 99%